2015
DOI: 10.1530/endoabs.37.gp.16.08
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and cardiac function in young adults with classical congenital adrenal hyperplasia

Abstract: Introduction: Patients with classical congenital adrenal hyperplasia (CAH) have increased cardiovascular risk, but the vascular and cardiac function during longitudinal corticoids replacement therapy is not known thoroughly. Material and methods: Cross-sectional study of 19 Caucasian adults with CAH (age 23.7 ± 3.8 years; twelve males) compared to 20 healthy volunteers matched for origin, sex, age, and body mass index (BMI). All of the participants were assessed for flow mediated dilatation of the brachial art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Doppler tissue imaging of our patients revealed defective LV ventricular relaxation, rise of the diastolic pressures pointing to possible impairment of early filling of the ventricles 15 . Our results match those of Wierzbicka‐Chmiel et al, 31 and those by Nengom et al, 41 Marra et al 32 and Mooij et al 33 The reduced average mitral s´ velocity in our cohort compared to controls also supports the presence of possibly altered LV systolic function. A reduced s´ velocity was previously documented in subclinical LV systolic dysfunction in patients with hypertrophied myocardium where the average s´ velocity was found to be a good representative of LV contractile function besides being an independent predictor of LV diastolic dysfunction despite normal LV ejection fraction 42 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Doppler tissue imaging of our patients revealed defective LV ventricular relaxation, rise of the diastolic pressures pointing to possible impairment of early filling of the ventricles 15 . Our results match those of Wierzbicka‐Chmiel et al, 31 and those by Nengom et al, 41 Marra et al 32 and Mooij et al 33 The reduced average mitral s´ velocity in our cohort compared to controls also supports the presence of possibly altered LV systolic function. A reduced s´ velocity was previously documented in subclinical LV systolic dysfunction in patients with hypertrophied myocardium where the average s´ velocity was found to be a good representative of LV contractile function besides being an independent predictor of LV diastolic dysfunction despite normal LV ejection fraction 42 .…”
Section: Discussionsupporting
confidence: 88%
“…Doppler tissue imaging of our patients revealed defective LV ventricular relaxation, rise of the diastolic pressures pointing to possible impairment of early filling of the ventricles. 15 Our results match those of Wierzbicka-Chmiel et al, 31 and those by Nengom et al, 41 Marra et al 32 and Mooij et al 33 The reduced average mitral Regarding RV, diastolic dysfunction was more pronounced in our patients with low tricuspid s´ velocity and e´/a´ ratio. It has been demonstrated that RV s´ velocity can additionally predict RV systolic function at ejection fractions below 45% with a sensitivity of 90% and specificity of 85%.…”
Section: Echocardiographysupporting
confidence: 91%
See 1 more Smart Citation
“…About 1% of the general population are using long-term GC therapy at any given time, due to the increased preva-lence of diseases requiring such therapy [2][3]. There is growing concern that markedly increased use of GCs can lead to supraphysiological GC exposure and may induce specific adverse cardio-metabolic complications, such as dyslipidaemia, adiposity and central obesity, decreased insulin sensitivity, hyperglycaemia and diabetes, inflammation, immune dysregulation and platelet activation, and finally hypertension and atherosclerosis followed by cardio-vascular derangements, such as increased risk of coronary artery disease, heart insufficiency, or stroke [4][5]. These exogenous Miłosz P. Kawa, Pomeranian Medical University, Al.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, miRNA-223, the expression of which is dependent on intracellular cholesterol levels, has also been reported to play a role in endothelium, especially due to the fact that miRNA-223 negatively regulates the inflammatory response by blocking the NLRP3 inflammasome and IL-1b production [22]. Altogether, it seems that the involvement of miRNAs in angiogenesis and endothelial cell function in cardiovascular system is substantial, making miRNAs presumably major governing forces in the pathogenesis of endothelial dysfunction developing GC-related complications have been strictly linked to increased cardio-vascular morbidity or mortality [4][5]. Nevertheless, there is no medical consensus on the best strategies for the prevention and detection of GC-induced complications, and available data on these adverse events are rather poor, with many of the clinical studies being inconclusive, resulting in the lack of optimal treatment strategies for patients affected with glucocorticoid-induced adverse cardio-metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%